Stomatin-like protein 2 is involved in endometrial stromal cell proliferation and differentiation during decidualization in mice and humans. Issue 2 (February 2017) - Feng, Qian; Hu, Zhuo-Ying; Liu, Xue-Qing; Zhang, Xue; Lan, Xi; Geng, Yan-Qing; Chen, Xue-Mei; He, Jun-Lin; Wang, Ying-Xiong; Ding, Yu-Bin
Abstract: The molecular mechanisms underlying endometrial stromal cell proliferation and differentiation (decidualization) are still not fully understood. This study revealed that increased Slp-2 expression is a significant factor modulating endometrial stromal cell proliferation and decidualization in both mice and humans. Our results showed a significant difference in the mRNA and protein levels between the implantation site and inter-implantation site on day 5 and day 6 of pregnancy in mice (all P < 0.05). Strong Slp-2 immunostaining was mainly localized within the decidual zone of mice through the post-implantation period. Mice with artificially induced deciduoma showed significantly higher expression of Slp-2 compared with uninduced controls ( P < 0.005). Human stromal cells in the middle and late-secretory phases demonstrated significantly (all P < 0.05) upregulated SLP-2, compared with cells in the proliferative phase and early secretory phases. Further analyses of the SLP-2 gene knocked down revealed a significant ( P < 0.005) repression of both the decidualization marker gene's expression (decidual/trophoblast prolactin-related protein in mice, insulin-like growth factor binding protein and prolactin in human) and the cell proliferation in in vitro-induced decidualized primary endometrial stromal cells in mice and humans.